Case report: Clinical fungal endocarditis as a component of presumptive systemic aspergillosis infection in a dog - Drake, L. Kay (Frontiers in Veterinary Science, 2025)
A 2-year-old 26-kilogram female spayed mixed breed dog presented for acute azotemia, a new heart murmur, anorexia, and lethargy. Further workup revealed marked azotemia with bilateral renal changes on abdominal ultrasound. An echocardiogram detected vegetative lesion on the mitral valve, consistent with infective endocarditis. The patient tested positive for the galactomannan antigen (Aspergillus EIA Galactomannan Test by MiraVista) leading to a presumptive diagnosis of systemic aspergillosis. Despite aggressive treatment, the patient continued to deteriorate and developed signs of dyspnea which temporarily improved with furosemide therapy (VetOne; Boise, ID). After humane euthanasia, postmortem evaluation confirmed fungal endocarditis. This is the first published case of clinical endocarditis in a dog suspected to be from aspergillosis based on both antemortem diagnostics and postmortem pathology. Thus, this case serves to further our understanding of systemic aspergillosis manifestations which in turn can aid in prompt diagnosis and treatment of the condition.